Analysis Internal Factors Of Bank Performance On Bank’s Profitability in Indonesia - Reskita, Liliani; -, Purwanto (Journal of Management and Leadership, 2019)
This research aims to analyze internal factor n bank performance was influenced by using macroeconomic factor as control variable. The determinants used for internal factor of bank consist of size, liquidity, capital and credit risk with control variable such as GDP and inflation. Quantitative method is used and for the sample suddenly stand up from 15 banks with specific criteria that include in Indonesia Stock Exchange. Based on the multiple regression conclude that concluded size, capital, credit risk and inflation have significant positive effect on Return on Asset, while liquidity and GDP have a significant negative effect on Return on Asset.